Hydronephrosis Associated With Pelvic Organ Prolapse: A Systematic Review. Issue 3 (March 2020) - Siddique, Moiuri; Ingraham, Caitlin; Kudish, Bela; Iglesia, Cheryl B.; Polland, Allison
Abstract : Objectives: The aim of this study was to report the prevalence of hydronephrosis associated with pelvic organ prolapse (POP). Methods: We conducted a MEDLINE and PubMed search from 1996 to October 2016 using PRISMA guidelines. Eight studies met criteria for inclusion, including 3 prospective and 5 retrospective studies. Results: The prevalence of hydronephrosis ranged from 3.5% to 30.6% in studies that included multiple stages of prolapse. Hydronephrosis correlated with prolapse severity in multiple studies, but serum creatinine did not consistently predict hydronephrosis. Two studies reported a significantly higher prevalence of hydronephrosis in patients with uterovaginal prolapse compared with vaginal vault prolapse. Complete resolution of hydronephrosis was described in 56% to 83% of patients after undergoing surgical treatment for advanced prolapse. Conclusions: Hydronephrosis among patients with POP is not rare, and we suggest consideration of upper tract evaluation in patients presenting with POP, particularly in those with advanced uterovaginal prolapse electing to proceed with expectant or conservative management.